Estudio de prefactibilidad para la elaboración de suplemento alimenticio a base de yacón (Smallanthus sonchifolius) - Chavez Rivera, Kevin Anthony (2022)
The present investigation evaluates the feasibility of implementing a plant producing a yacon-based supplement in powder form, which aims to improve the quality of life of its consumers thanks to its regulatory functions. The market study was carried out in the socioeconomic status A, B and C of zones 6 and 7 of metropolitan Lima to determine the specific demand of the project. In addition, thanks to the results, the sales channels were defined, which are retail stores and direct sales. We also established that the product will be offered in 350-gram packages at a price of 30 soles (including taxes) to the final consumer in the first year. On the other hand, thanks to the ranking of factors it was established that the best location for the installation of the plant is the district of Chilca, belonging to the province of Cañete; this decision was taken because this location will present costs savings in the land and in the basic services. To establish the production process, scientific articles were taken as reference, as well as laboratory studies to determine the critical variables to be considered to preserve the safety of the product. Likewise, production in the first year will be 198,011 packages of finished product. By the economic evaluation of the project, it was determined that the investment to start is S/2,655,893 soles, of which 64% is the equity and 36% will be financed through a loan with a APR of 20%. Finally, the financial VNA was determined at S/825,210, the IRRF was 44.85%, the B/C was 1.50 and the recovery period was approximately 3 years and 8 months.